Akt/mTOR signalling in myelination. (18th July 2013) - Norrmén, Camilla; Suter, Ueli
Abstract : Akt signalling has emerged as one of the major pathways involved in myelination, implicated in the regulation of several steps during the development of myelinating Schwann cells and oligodendrocytes. One of the main pathways intimately linked with Akt is mTOR [mammalian (or mechanistic) target of rapamycin] signalling. Recent evidence suggests that many processes attributed to the Akt pathway in myelination depend, at least partly, on mTOR signalling. In the present mini-review, we summarize the major aspects of Akt/mTOR signalling and myelination, and how they appear to be linked. We focus on the PNS (peripheral nervous system), but also cover the key points of CNS (central nervous system) myelination, pointing out differences and similarities between the PNS and the CNS.